2021
DOI: 10.1093/jhps/hnab008
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of acetabular wall indices: comparison between CT and plain radiography

Abstract: The purpose of this study was to compare measurements of anterior wall index (AWI) and posterior wall index (PWI) on computed tomography (CT) to those on radiographs (XR). A consecutive cohort of 33 patients (45 hips total) being evaluated for hip pain with both XR and CT was examined. Preoperative measurements of AWI and PWI were performed utilizing supine anteroposterior pelvic XR and coronal and swiss axial CT scans by two independent raters. Mean differences between XR and CT measurements were compared, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In this case, the anterior coverage of the hip joint was greatly overestimated on the pelvic AP radiograph because of the effect of the AIIS. This can also explain why there is only a moderate correlation between AWI on pelvic radiographs and CT. [39] In the same patient, after the acetabulum was reoriented in PAO, the supporting area of the acetabulum rotated laterally and anteriorly. As the anterior hip coverage signi cantly increased, the ACEA increased signi cantly as well (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…In this case, the anterior coverage of the hip joint was greatly overestimated on the pelvic AP radiograph because of the effect of the AIIS. This can also explain why there is only a moderate correlation between AWI on pelvic radiographs and CT. [39] In the same patient, after the acetabulum was reoriented in PAO, the supporting area of the acetabulum rotated laterally and anteriorly. As the anterior hip coverage signi cantly increased, the ACEA increased signi cantly as well (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…However, some authors have reported that values of radiographic acetabular wall indices are consistently larger for AWI and smaller for PWI relative to CT-based measurements of the same indices and that a standardization of measurements is needed. 24 Radiographic ACEA has traditionally been used to quantify anterior coverage, with normal values ranging from 25°to 40°. 8,22 A recent multicenter prospective cohort study suggested that obtaining a false-profile radiograph adds strong value to the diagnosis of hip dysplasia in the young adult in cases that would otherwise remain missed with a single anteroposterior view.…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors have reported that values of radiographic acetabular wall indices are consistently larger for AWI and smaller for PWI relative to CT-based measurements of the same indices and that a standardization of measurements is needed. 24…”
Section: Discussionmentioning
confidence: 99%
“…Thus, low-dose CT assessment appears to offer critical insight into anterior coverage and deficiency that is not gained from plain radiographs alone. Nazaroff et al 25 previously attempted to correlate measurements of AWI and PWI on plain radiographs to similar measurements made on CT in a general population. They found a moderate correlation between the 3D and plain radiographic measurements for the AWI, while a poor correlation was seen for the PWI.…”
Section: Discussionmentioning
confidence: 99%